Pengaruh Green Marketing Mix terhadap Brand Image Produk Tupperware - Genoveva Genoveva; Wulan Berliana (Research Center and Case Clearing House PPM School of Management, 2021)
The rapid growth of the industrial has an impact on social and environmental problems, one of which is global warming. Society as a group of consumers who care about their environment and are responsible for environmental damage is called the Green Consumer. With the Green Consumer, the company is expected to be able to create marketing processes that pay more attention to the environment and have a positive impact on brand image. This study aims to determine the effect of green marketing mix partially and simultaneously on brand image on Tupperware products. The independent variables in this study consisted of green product (X1), green price (X2), green place (X3), and green promotion (X4) with the dependent variable brand image (Y). This research is a quantitative study with descriptive data analysis, using multiple linear regression to determine the significance and probability of the effect of independent variables on the dependent variable. The population in this study are consumers who use Tupperware products in Java. The sample in this study amounted to 200 respondents using purposive sampling through an online questionnaire. The results showed that the green product, green price and green place variables significantly affected the Tupperware product brand image. While the green promotion variable does not have an influence on the Tupperware product brand image. Green Price gives the biggest contribution to Brand Image, therefore, the company should be pay special attention to price factors that greatly affect Brand Image, especially for long-term environmental factors